Clinical profile of individuals with Down Syndrome in APAES in cities in the South of Minas Gerais (Research, Society and Development, 2022)
Down Syndrome (DS) is related to abnormalities of the respiratory, cardiovascular, sensory (organs), gastrointestinal, hematological, immune, renal, and genitourinary systems. The present work analyzes the profile of DS cases in APAE's (Association of Parents and Friends of the Exceptional) located in cities in southern Minas Gerais (Machado, Varginha and Ilicínea). Data was obtained through a questionnaire, which showed: diagnosis, age, sex, place of birth of the carrier patient, history of the current disease, past pathological history, physiological history, family history and social history. Data were tabulated and all variables were analyzed descriptively. The sample comprised 42 participants, with varied ages (minimum: 4 months; maximum: 43 years). The results obtained showed 25 males and 17 females. We observed a minimum maternal age at delivery of 19 years and a maximum of 45 years, and most were in the 30 to 39 age group. Past pathological history showed 10 participants with heart disease, 9 with phonoaudiological alterations, 6 with hypothyroidism. Gastrointestinal, hematological, immunological, renal, and genitourinary alterations were absent. Regarding social history, only 2 presented socialization difficulties. Most of those evaluated presented psychomotor difficulties, but with calm behavior and good social interaction. The results of this research allowed us to obtain epidemiological and clinical information, aiming to anticipate the detection of complications in populations with DS at risk and to reduce the mortality rate, especially in children.